(untitled) (Desarrollo, Estado y Espacio, 2024)
In this article we propose to problematize the construction of public policies in agroecology based on a reflection situated around the agroecology forums that took place during 2019 in the province of Entre Ríos, Argentina. Likewise, we reflect on its institutionalization processes and focus on understanding agroecological transitions by analyzing the will to change and the category of forced transitions. To do this, we carry out a historical analysis and put into play a qualitative methodological strategy that is supported by open, semi-structured interviews and field notes based on my active participation in the discussion forums. We seek to contribute to the field of policy construction and interventions in agroecology, as a way of understanding the development of rural territories and food production.